Tax Aggressiveness Determinant: Evidence on Consumer Non-Cyclicals Sector - Kurnia; Ninit Megalia Pransisca (Jurnal Akuntansi, 2025)
Tax Aggressiveness can be interpreted as minimising the tax expenses paid aggressively. The primary goal of this research is to analyse and acquire proof of the influence of related party transactions, advertising expenses, and executive compensation on tax aggressiveness at companies from the consumer non-cyclical sector listed on the Indonesia Stock Exchange from 2017 until 2021. The method used for sample selection is purposive sampling, which obtained 18 samples, totalling 90 observations. The research used a quantitative approach and panel data regression analysis technique. The outcomes of this research show that related party transactions, advertising expenses, and executive compensation simultaneously influence tax aggressiveness. According to the partial test, the results showed that the related party transaction negatively influences tax aggressiveness. In contrast, advertising expenses and executive compensation do not influence tax aggressiveness.